2020
DOI: 10.3390/cells9122626
|View full text |Cite
|
Sign up to set email alerts
|

Function of TREM1 and TREM2 in Liver-Related Diseases

Abstract: TREM1 and TREM2 are members of the triggering receptors expressed on myeloid cells (TREM) family. Both TREM1 and TREM2 are immunoglobulin superfamily receptors. Their main function is to identify foreign antigens and toxic substances, thereby adjusting the inflammatory response. In the liver, TREM1 and TREM2 are expressed on non-parenchymal cells, such as liver sinusoidal endothelial cells, Kupffer cells, and hepatic stellate cells, and cells which infiltrate the liver in response to injury including monocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 124 publications
(110 reference statements)
1
29
0
1
Order By: Relevance
“… 41 An important additional amplifier of TLR4-mediated hepatic inflammation is the TREM1/DAP12 pathway. 23 , 24 , 25 Interestingly, we here report that the prevention of liver inflammation and injury mediated by the targeting of 3BP2 or SYK strongly decrease TREM1/DAP12 expression. Because of the central place of the SYK pathway in both TLR4 and TREM-1 signaling, 23 this suggests the establishment of an inflammatory loop in which SYK and its partner 3BP2 exacerbate liver inflammation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“… 41 An important additional amplifier of TLR4-mediated hepatic inflammation is the TREM1/DAP12 pathway. 23 , 24 , 25 Interestingly, we here report that the prevention of liver inflammation and injury mediated by the targeting of 3BP2 or SYK strongly decrease TREM1/DAP12 expression. Because of the central place of the SYK pathway in both TLR4 and TREM-1 signaling, 23 this suggests the establishment of an inflammatory loop in which SYK and its partner 3BP2 exacerbate liver inflammation.…”
Section: Discussionmentioning
confidence: 63%
“…This effect of the hepatic inflammation was also confirmed by the decreased hepatic expression of CD44 and SYK at the protein level (Figure 3H) and decreased serum level of CCL2 (Figure 3I). In addition, the hepatic expression of Trem1, an important amplifier of TLR4 pathway via SYK activity, 15,[23][24][25] decreased in MCDD-fed Sh3bp2 -/mice compared with MCDD-fed Wt mice (Figure 3G). In line with this, the expression of Dap12, the transmembrane adaptor required for TREM1 function, also decreased (Figure 3G).…”
Section: Hepatic Expression Of 3bp2 and Syk Correlated With Liver Complications In Mouse Models Of Mafldmentioning
confidence: 99%
See 1 more Smart Citation
“…As members of the triggering receptors expressed on myeloid cells (TREM) family, TREM1 and TREM2 participate in the regulation of inflammation and immune response by modulating the secretion of inflammatory cytokines such as TNF-α, IL-1β, and IL-6. 30 Recent studies have indicated that the missense mutation and expression changes of TREM1 and TREM2 are closely related to cognitive dysfunction in patients with AD. 31 , 32 Clinical studies have shown that the level of TREM2 in the peripheral blood of patients with AD increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Os macrófagos, em geral, expressam outras moléculas importantes e determinantes na sua polarização em M1 ou M2 como TREM1 (Triggering Receptor Expressed on Myeloid Cells-1), o TIM3 (T cell immunoglobulin and mucin domain-3) e a galectina 9. O TREM1 é um receptor da família das imunoglobulinas, com função principal de identificar antígenos, modulando a resposta inflamatória (Sun et al, 2020).…”
Section: Perfil Fenotípico De Macrófagosunclassified